Locating surface deformation induced by earthquakes using GPS, GLONASS and Galileo ionospheric sounding from a single station. Issue 8 (15th October 2021) - Zedek, Florian; Rolland, Lucie M.; Mikesell, T. Dylan; Sladen, Anthony; Delouis, Bertrand; Twardzik, Cédric; Coïsson, Pierdavide
Highlights: One single GNSS station can locate the origin of a coseismic TEC perturbation. A dual-frequency multi-GNSS station acts as an array of ionospheric receivers. Increasing the number of GNSS satellites increases the precision of the localization. Abstract: Monitoring earthquakes to rapidly forecast their consequences remains a challenging task, especially in areas far from seismic and geodetic networks. Large and shallow earthquakes induce disturbances in the ionospheric Total Electron Content (TEC). These disturbances are commonly detected using Global Navigation Satellite Systems (GNSS) stations that can sound the ionosphere at great distances. To address this instrumentation sparsity issue, we assess a single GNSS station's ability to constrain the origin location of a coseismic ionospheric disturbance (CID) using observations of TEC. We develop a grid-search method that explores different trial origins (i.e. source locations) to determine which synthetic CID signal best matches the observed TEC time series. We confirm that a larger number of monitoring satellites enhances the opportunity to have the favorable geometrical coverage of satellites needed to resolve CID origins. We use TEC data acquired during two earthquakes having different moment magnitudes: a Mw 7.1 from Turkey and a Mw 7.8 from New Zealand. Using a well-placed multi-GNSS station we are able to retrieve the CID origin with an accuracy of 50 km and a theoretical precision of the same order. We conclude that a very sparse network of multi-GNSS stations can provide an independent estimate of the spatial distribution of large scale coseismic motions, including offshore areas 200–300 km from the coastline.